Reticulocyte Maturation and Variant Red Blood Cells - Stevens-Hernandez, Christian J.; Flatt, Joanna F.; Kupzig, Sabine; Bruce, Lesley J. (Frontiers in Physiology, 2022)
The bone marrow produces billions of reticulocytes daily. These reticulocytes mature into red blood cells by reducing their plasma membrane by 20% and ejecting or degrading residual internal organelles, membranes and proteins not required by the mature cell. This process occurs by autophagy, protein degradation and vesiculation but is not well understood. We previously reported that Southeast Asian Ovalocytic RBCs demonstrate incomplete reticulocyte maturation and we have now extended this study to a number of other variant RBCs. By comparing the profile of a pure reticulocyte preparation of cultured red cells with these variant cells, we show that the largest of these cells, the overhydrated hereditary stomatocytosis cells, are the least mature, they barely reduced their plasma membrane and contain large amounts of proteins that should have been reduced or removed. Intermediate sized variant RBCs appear to be more mature but retain some endoplasmic reticulum and residual membrane proteins. We propose that the size and composition of these variant cell types correlate with the different stages of reticulocyte maturation and provide insight into the reticulocyte maturation process.